Service Quality Model Outpatient in State Hospital Based on Community Satisfaction Index and Healthqual Using Interpretative Structural Modeling - Astuti, Herni Justiana; Santoso, Suryo Budi; Dwiyanti, Retno (Journal of Cultural Analysis and Social Change, 2025)
Public hospitals must continuously improve service quality to meet patient expectations while maintaining public accountability. However, existing service quality models such as SERVQUAL and the Community Satisfaction Index (CSI) are not fully capable of capturing the complex and sensitive nature of healthcare experiences, where patients interact under physical and emotional stress. This study aims to develop an integrated service quality model for state hospitals by combining the CSI and HealthQual frameworks through the Interpretative Structural Modeling (ISM) approach. Data were collected from experts in marketing, hospital management, and healthcare services across four districts to identify and structure the key determinants of service quality. The findings reveal five major dimensions empathy, physical evidence, security, reliability, and outcome improvement comprising twenty-seven indicators. Among these, employee politeness, detailed explanation to patients, medical equipment safety, and diagnostic accuracy are identified as the most critical factors influencing patient satisfaction. This integrated model offers a systematic framework for policymakers and hospital managers to enhance patient-centered care, strengthen diagnostic reliability, and improve overall service accountability within public healthcare organizations.